Nitrogen deprivation elicits dimorphism, capsule biosynthesis and autophagy in Papiliotrema laurentii strain RY1. (September 2019) - Sarkar, Soumyadev; Mukherjee, Avishek; Das, Subhadeep; Ghosh, Bidisha; Chaudhuri, Shouvik; Bhattacharya, Debanjana; Sarbajna, Arpita; Gachhui, Ratan
Highlights: Surface and ultrastructural modifications in Papiliotrema laurentii strain RY1 under nitrogen starvation. Cell-to-hyphae transition observed under nitrogen deprivation. Capsule biosynthesis occurred upon nitrogen limitation. Nitrogen starvation in Papiliotrema laurentii strain RY1 induced autophagy. Abstract: Stress response due to the lack of essential nutrient(s) for an organism has been a focal point of several scientific investigations. The present study investigates the cellular adaptations behind the ability of Papiliotrema laurentii strain RY1 to perpetuate without added nitrogen and propagate robustly in growth- limiting amount of nitrogen. We executed phenotypic (using scanning electron microscopy, differential interference contrast microscopy and transmission electron microscopy), microbiological and computational analyses to show multiple responses of dimorphism, capsule formation and autophagy as a survival strategy by the yeast upon nitrogen starvation. The roles of phosphomannose isomerase, phosphomannomutase and several autophagy-related transcripts aiding in such a response have been discussed.